A tour at national museum using desktop virtual reality / Nurul Syafiqah Ismail - Ismail, Nurul Syafiqah (2018)
A tour at National Museum using Desktop Virtual Reality presents a tool for users to view the artefacts at the museum in 3D view. It is for those who have trouble to go to the museum for whatever reasons. To make sure the user could get the information about the artefacts as they were in the museum, the use of 3D are applied sto bring them the presence of the object itself. The detailed in 3D views and the information about the artefacts that this project can give is the measure to the user to recognize that it can give them information same as the real museum. The user just need to walk around in the 3D environment and if they want to get the information about the object, they just need to touch the specific object and it will give the detailed info about it. The evaluation obtained from the school students who still learning history where this project could be their reference in their learning process. The result from the evaluation used for fixing the project if there is some problem happen.